Bacterial Community and PHB-Accumulating Bacteria Associated with the Wall and Specialized Niches of the Hindgut of the Forest Cockchafer (Melolontha hippocastani) - Alonso-Pernas, Pol; Arias-Cordero, Erika; Novoselov, Alexey; Ebert, Christina; Rybak, Jürgen; Kaltenpoth, Martin; Westermann, Martin; Neugebauer, Ute; Boland, Wilhelm (Frontiers in Microbiology, 2017)
Abstract A characterization of the bacterial community of the hindgut wall of two larval and the adult stages of the forest cockchafer (Melolontha hippocastani) was carried out using amplicon sequencing of the 16S rRNA gene fragment. It was found that, in second-instar larvae, Caulobacteraceae and Pseudomonaceae showed the highest relative abundances, while in third-instar larvae, the dominant families were Porphyromonadaceae and Bacteroidales-related. In adults, an increase of the relative abundance of Bacteroidetes, Proteobacteria (γ- and δ- classes) and the family Enterococcaceae (Firmicutes) was observed. This suggests that the composition of the hindgut wall community may depend on the insect’s life stage. Additionally, specialized bacterial niches hitherto very poorly described in the literature were spotted at both sides of the distal part of the hindgut chamber. We named these structures “pockets”. Amplicon sequencing of the 16S rRNA gene fragment revealed that the pockets contained a different bacterial community than the surrounding hindgut wall, dominated by Alcaligenaceae and Microccoccaceae-related families. Poly-β-hydroxybutyrate (PHB) accumulation in the pocket was suggested in isolated Achromobacter sp. by Nile Blue staining, and confirmed by gas chromathography–mass spectrometry analysis (GC-MS) on cultured bacterial mass and whole pocket tissue. Raman micro-spectroscopy allowed to visualize the spatial distribution of PHB accumulating bacteria within the pocket tissue. The presence of this polymer might play a role in the colonization of these specialized niches.